Subsistência, expressão cultural e conflito : uma análise do uso dos artesanatos pelos Pataxó em Belo Horizonte - MG - Caroline Domingues Silva da Costa (2023)
The present work aims to analyze the use of handicrafts by the Pataxó indigenous people in the city of Belo Horizonte based on interviews carried out in 2019, being understood as cultural instruments and, at the same time, a source of income, thus constituting a link between the village and the city. For this, literature was used that spoke to the objectives of the work and discussed the following themes: crafts, indigenous people in cities and, more specifically, Pataxó crafts. The research, of a qualitative nature, had its methodology based on Thematic Analysis. Based on this methodology, using secondary data, I analyzed interviews carried out with Pataxó indigenous people who lived in Aldeia Naô Xohã, located in the Metropolitan Region of Belo Horizonte. Based on the analysis of the interviews, the Pataxó's reports allowed us to find three facets of handicrafts: handicrafts as a possibility for work and subsistence; crafts as an expression of their culture; and crafts as a marker of conflicts in the city. The results pointed to the importance of selling handicrafts as a form of subsistence in the city, in addition to demonstrating how these economic activities trigger various situations of conflict between indigenous and non-indigenous people.